2023
DOI: 10.3390/polym15244666
|View full text |Cite
|
Sign up to set email alerts
|

Alginate–Moroccan Clay, New Bio-Nanocomposite for Removal of H2PO4−, HPO42−, and NO3− Ions from Aqueous Solutions

Rachid Aziam,
Daniela Simina Stefan,
Abdelali Aboussabek
et al.

Abstract: The aim of this work is to synthesize and characterize alginate–Moroccan clay bio-composite in order to improve our understanding of the adsorption of inorganic pollutants found in textile effluents. Characterization of the bio-composite used was carried out using a variety of techniques (IR-TF, SEM, DRX, and pHZPC). The influence of the medium’s physico-chemical parameters (temperature, pH, initial concentration, etc.) on the retention of inorganic pollutants was also studied. Studies of adsorption and inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…The natural clay used in this study was analyzed and characterized by [37]. They showed that natural clay can be identified by two aspects, according to SEM images as follows: the distributed powder and the creation of a few agglomerates with varying forms.…”
Section: Characterization Of Bio-nanocomposite Beadsmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural clay used in this study was analyzed and characterized by [37]. They showed that natural clay can be identified by two aspects, according to SEM images as follows: the distributed powder and the creation of a few agglomerates with varying forms.…”
Section: Characterization Of Bio-nanocomposite Beadsmentioning
confidence: 99%
“…These agglomerates are created at higher magnifications by the assembling of microscopic particles with varying forms and a heterogeneous morphology. The agglomerate shapes depicted in Figure 1 are distinguished by the substantial number of pores distributed across the entire surface area of the natural clay employed [37].…”
Section: Characterization Of Bio-nanocomposite Beadsmentioning
confidence: 99%